The Principal's Role in Improving Teacher Performance Ability - barkatullah amin (Tajdid Al-Athfal, 2021)
Leaders have a dominant role in an organization. The main task of a leader is to deliver all the components involved to achieve a common goal. The principal has the role and duties of Educator, Manager, Administrator, Innovator, Motivator, Supervisor, Leader as a reliable leader. This study aims to find out the role of the principal in improving teacher performance. This study uses descriptive method with data collection through selected observations. The results showed that having a very important and strategic role in order to improve the quality of education, it can influence whether or not it succeeds as well as the backbone in efforts to improve the quality of education in the school it leads, play an active role as a spirit generator, encourage, pioneering and establishing as well as as an administrative manager, in other words the principal is one of the driving motors of a formidable education management as well as quality.